Mycobacterial DNA extraction for whole-genome sequencing from early positive liquid (MGIT) cultures - Votintseva, Antonina A; Pankhurst, Louise J; Anson, Luke W; Morgan, Marcus R; Gascoyne-Binzi, Deborah; Walker, Timothy M; Quan, T Phuong; Wyllie, David H; Del Ojo Elias, Carlos; Wilcox, Mark; Walker, A Sarah; Peto, Tim E A; et al. (Journal of clinical microbiology, 2015)
We developed a low-cost and reliable method of DNA extraction from as little as 1 ml of early positive mycobacterial growth indicator tube (MGIT) cultures that is suitable for whole-genome sequencing to identify mycobacterial species and predict antibiotic resistance in clinical samples. The DNA extraction method is based on ethanol precipitation supplemented by pretreatment steps with a MolYsis kit or saline wash for the removal of human DNA and a final DNA cleanup step with solid-phase reversible immobilization beads. The protocol yielded ≥0.2 ng/μl of DNA for 90% (MolYsis kit) and 83% (saline wash) of positive MGIT cultures. A total of 144 (94%) of the 154 samples sequenced on the MiSeq platform (Illumina) achieved the target of 1 million reads, with <5% of reads derived from human or nasopharyngeal flora for 88% and 91% of samples, respectively. A total of 59 (98%) of 60 samples that were identified by the national mycobacterial reference laboratory (NMRL) as Mycobacterium tuberculosis were successfully mapped to the H37Rv reference, with >90% coverage achieved. The DNA extraction protocol, therefore, will facilitate fast and accurate identification of mycobacterial species and resistance using a range of bioinformatics tools.